2017
DOI: 10.1088/1361-6528/aa8a5b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-oxide-wrapped ZnMn2O4 as a high performance lithium-ion battery anode

Abstract: Cation distribution between tetrahedral and octahedral sites within the ZnMn2O4 spinel lattice, along with microstructural features, is affected greatly by the temperature of heat treatment. Inversion parameter can easily be tuned, from 5 to 19%, depending on the annealing temperature. The upper limit of inversion is found for T= 400 °C as confirmed by X-ray powder diffraction and Raman spectroscopy. Excellent battery behavior is found for samples annealed at lower temperatures; after 500 cycles the specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The Raman spectrum of EDM grown from the solution containing 4 mM MnSO 4 and 0.1 M ZnSO 4 (Figure 8, blue plot) is different from that of EDM electrodeposited in the absence of Zn 2+ . The bands at ≈318, 370, and 668 cm −1 are compatible with tetragonal spinel ZnMn 2 O 4 [ 62–67 ] and those at ≈ 500, 574, and 658 cm −1 with δ‐MnO 2 . [ 68 ] Spectral assignment on the basis of the literature cannot be definitive, and a rigorous structural analysis is beyond the scope of this paper, but the profoundly modified pattern witnesses a strong effect of Zn 2+ on the electrocrystallization of EDM.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectrum of EDM grown from the solution containing 4 mM MnSO 4 and 0.1 M ZnSO 4 (Figure 8, blue plot) is different from that of EDM electrodeposited in the absence of Zn 2+ . The bands at ≈318, 370, and 668 cm −1 are compatible with tetragonal spinel ZnMn 2 O 4 [ 62–67 ] and those at ≈ 500, 574, and 658 cm −1 with δ‐MnO 2 . [ 68 ] Spectral assignment on the basis of the literature cannot be definitive, and a rigorous structural analysis is beyond the scope of this paper, but the profoundly modified pattern witnesses a strong effect of Zn 2+ on the electrocrystallization of EDM.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the zinc ions in ZnMn 2 O 4 crystals are exposed to large electrostatic repulsive forces when moving, thus making them move extremely slowly and seriously hindering the electrochemical performance of ZnMn 2 O 4 . 19 Chen et al found that reducing the size of the active material to the nanoscale effectively improved ion diffusion and electron migration, leading to significantly shorter diffusion paths for the guest ions, generating abundant lattice defects 20 and thus improving the electrochemical performance. Meanwhile, they proposed that N-doping of graphene exhibited good conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the assembly of ZIBs can be done in air, offering reduced fabrication complexity. A ZIB typically consists of a zinc metal anode, a porous separator with a low hazard electrolyte and various metal oxides such as V 2 O 5 (Javed et al, 2020), ZnMn 2 O 4 (Sun et al, 2017), manganese (IV) oxide (MnO 2 ) [Jiao et al, 2020) and manganese (II, III) oxide (Mn 3 O 4 ) (Hao et al, 2018)] as the cathode. The metal zinc anode has a high theoretical capacity of 820 mAh g −1 (Wang F. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%